Effectiveness of distance education program on mothers' empowerment in exclusive breastfeeding: A randomized clinical trial - Zeynab Taheri; Fatemeh Bakouei; Mouloud Agajani Delavar; Mahbobeh Faramarzi; Afsaneh Bakhtiari; Fatemeh Nasiri Amiri (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Mothers need the necessary skills to be empowered in successful breastfeeding. This study aimed to investigate effectiveness of the distance education program on the mothers' empowerment in exclusive breastfeeding. MATERIALS AND METHODS: A randomized clinical trial study was done on 72 nulliparous pregnant women 28-32 weeks with normal pregnancy. The qualified women were randomly assigned to the intervention and control groups based on the random-number table. The breastfeeding training packages were sent to women in the intervention group via Telegram every week from 32 until 37 weeks of gestation. The mothers' empowerment in breastfeeding (primary outcome) and the exclusive breastfeeding rate (secondary outcome) were assessed by questionnaires. RESULTS: Based on the repeated measured tests, although scores for all domains and also the total score of the mothers' empowerment in breastfeeding between two groups had increased during the study period, there was a significant difference between the increasing trends of the maternal empowerment domains in two groups (interaction P value '0.001). Also, the prevalence of exclusive breastfeeding (secondary outcome) at 6 months was significantly higher in the intervention group (81.8% and 57.1% in the intervention and control groups, respectively) (P = 0.028). CONCLUSION: Distance education could increase all domains of the mothers' empowerment in breastfeeding after delivery. Also, exclusive breastfeeding at 6 months after delivery was significantly higher in mothers who were receiving the distance education packages.